Formulasi Strategi Bisnis Transportasi Online Untuk Meningkatkan Jumlah Pelanggan (Studi Pada Komunitas Pengemudi Ojek Online Gojek Di Kabupaten Cilacap Dan Banyumas) - Nashrullah (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This research aims to analyze the formulation of GOJEK's online transportation business strategy in order to increase the number of customers in Cilacap and Banyumas Regencies. Method: This research uses a qualitative approach. Data was collected through interviews, observation and documentation of research subjects and objects. The interview results, which were entered into the Business Model Canvas (BMC) table, were analyzed using the content analysis method. Research Findings: Based on the results of research and discussion, strategies that can be implemented by GOJEK drivers based on BMC include focusing and expanding customer segments, increasing value propositions, customer relationships, key partnerships, distribution channels, and optimizing key resources. In addition, optimization of key activities, revenue streams and cost structures was carried out to increase competitiveness and profitability. Theoretical Contribution: This research contributes to the field of online transportation business strategy by using the Business Model Canvas (BMC) as an effective analytical tool to formulate strategies for increasing customer numbers. Implications for Practitioners: It is hoped that the results of this research can be a reference for GOJEK drivers and other online transportation drivers in developing effective strategies to increase the number of customers and income. Research Limitations: This research has limitations in its coverage. It only focuses on Cilacap and Banyumas Regencies, so the results may not be fully generalizable to other regions. Apart from that, this research only uses a qualitative approach without any quantitative analysis, which can provide a broader perspective.